The importance of OCT angiography and Doppler ultrasound methods in diagnosis of optic neuropathies - Kaloshina, A A; Sheremet, N L (Vestnik oftal'mologii, 2022)
This review of literature presents an assessment of circulatory disorders of the optic nerve and the retina in patients with optic neuropathy of different origin by ultrasound and OCTA methods, outlines basic principles of analyzing the state of blood flow in the ocular vessels, and analyzes the results of Russian and foreign research on this topic.This review of literature presents an assessment of circulatory disorders of the optic nerve and the retina in patients with optic neuropathy of different origin by ultrasound and OCTA methods, outlines basic principles of analyzing the state of blood flow in the ocular vessels, and analyzes the results of Russian and foreign research on this topic.